The diversity of moulds in the candied salak (Salacca edulis Reinw.) - RATIH DHAMAYANTI; SURANTO SURANTO; RATNA SETYANINGSIH (Biodiversitas Journal of Biological Diversity, 2002)
The aims of this research were to identify moulds in candied fruit within three varieties of salak (i.e. sleman, gading and pondoh), and to know the effect of sugar concentration added, the time of storage, and additional of preservative chemical substance (benzoic acid) for the diversity of moulds in candied salak. The isolation method of moulds was used direct plating. In order to determine the kind of moulds, which tolerance in sugar solution (osmotic pressure), the samples were put on the surface of glucose 25% peptone yeast-extract agar (GPYA) medium, and then incubated at 30oC for seven days. After that the colony was transferred on potato dextrose agar (PDA) and czapeks dox agar (CDA) identification media. The results indicated that there were 10 different kind of moulds can be found in all samples, namely Aspergillus flavus, A, niger, A. versicolor, A. fumigatus, Aspergillus sp., Monilia sp., Mucor sp., Penicillium sp., Rhizopus sp. and Wallemia sp. In order to examine the influence of sugar concentration on the growth of moulds, the candied salaks were treated in different concentration. Candied salak with or without additional benzoicacid were treated with sugar concentration of 200 g/l, 250 g/l and 300 g/l. The highest concentration of sugar showed to lowest diversity of moulds for varieties of sleman and gading, conversely for variety of salak pondoh, the additionalof high sugar concentration showed increase in their diversity. The diversity of moulds in day of seventh was smallerthan the diversity of moulds in day of null. The concentration of benzoic acid (1 g/l) confined the diversity of moulds.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: candied salak, osmotic pressure, diversity of mould.